The Effect of iPS-Derived Neural Progenitors Seeded on Laminin-Coated pHEMA-MOETACl Hydrogel with Dual Porosity in a Rat Model of Chronic Spinal Cord Injury. Issue 4 (April 2019) - Ruzicka, Jiri; Romanyuk, Nataliya; Jirakova, Klara; Hejcl, Ales; Janouskova, Olga; Machova, Lucia Urdzikova; Bochin, Marcel; Pradny, Martin; Vargova, Lydia; Jendelova, Pavla
Spinal cord injury (SCI), is a devastating condition leading to the loss of locomotor and sensory function below the injured segment. Despite some progress in acute SCI treatment using stem cells and biomaterials, chronic SCI remains to be addressed. We have assessed the use of laminin-coated hydrogel with dual porosity, seeded with induced pluripotent stem cell-derived neural progenitors (iPSC-NPs), in a rat model of chronic SCI. iPSC-NPs cultured for 3 weeks in hydrogel in vitro were positive for nestin, glial fibrillary acidic protein (GFAP) and microtubule-associated protein 2 (MAP2). These cell-polymer constructs were implanted into a balloon compression lesion, 5 weeks after lesion induction. Animals were behaviorally tested, and spinal cord tissue was immunohistochemically analyzed 28 weeks after SCI. The implanted iPSC-NPs survived in the scaffold for the entire experimental period. Host axons, astrocytes and blood vessels grew into the implant and an increased sprouting of host TH + fibers was observed in the lesion vicinity. The implantation of iPSC-NP-LHM cell-polymer construct into the chronic SCI led to the integration of material into the injured spinal cord, reduced cavitation and supported the iPSC-NPs survival, but did not result in a statistically significant improvement of locomotor recovery.